Physical Education and Sport in Romania: Between Ideal, Reality, and Prospects for Reform - PRODEA, Cosmin; ȘTEFĂNESCU, Leonida Horea; ZANCA, Raoul Ștefan (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Physical Education and Sport (PES) represent a foundational pillar in contemporary educational architecture, supporting the holistic development of individuals. This study provides an integrative analysis of the educational ideal in this field, the systemic realities in Romania, and potential directions for reform, benchmarked against European best practices. Through a comparative approach, it highlights the convergences and divergences between Romania and other countries in Central, Southeastern, and Baltic Europe, offering a reflective framework for developing a sustainable, inclusive, and student-centered physical education. REZUMAT. Educația fizică și sportul în România: între ideal, realitate și perspective de reformă. Educația fizică și sportul (EFS) constituie un pilon fundamental în arhitectura educațională contemporană, susținând dezvoltarea integrală a individului. Studiul de față oferă o analiză integrativă a idealului educațional în domeniu, a realităților sistemice din România și a direcțiilor posibile de reformă, raportate la bune practici europene. Printr-o abordare comparativă, sunt evidențiate convergențele și diferențele dintre România și alte state din Europa Centrală, de Sud-Est și din regiunea baltică, oferindu-se un cadru de reflecție asupra dezvoltării unei educații fizice sustenabile, incluzive și centrate pe elev. Cuvinte-cheie: educație fizică, reformă curriculară, comparație internațională, politici educaționale, sănătate publică. Article history: Received 2025 May 26; Revised 2025 July 03; Accepted 2025 July 05; Available online 2025 July 30; Available print 2025 August 30